MORPHOMETRY OF PEDICLES OF LUMBAR VERTEBRAE IN ADULT INDIAN POPULATION: STUDY IN DRY HUMAN BONES (Asian Journal of Medical Research and Health Sciences, 2026)
The lumbar vertebrae are the five vertebrae located in the lower back, numbered L1 through L5. They are the largest vertebrae in the spine and are crucial for supporting the weight of the upper body, providing stability, and allowing for movement. They are characterized by their large, kidney-shaped vertebral bodies, which are designed to bear significant weight. The largest part of the vertebra, designed to withstand compressive forces. The lumbar vertebrae have strong bony elements, including the vertebral arch, which protects the spinal cord and nerve roots. The Vertebral Arch protects the spinal cord and nerves. The Facet Joints allow for movement between vertebrae. They also feature various processes (bony projections) that serve as attachment points for muscles and ligaments. The Spinous Processes are projections that can be felt as the "knobs" of the spine. The Transverse Processes are projections that serve as attachment points for muscles and ligaments. The Intervertebral Discs are located between the vertebrae, acting as shock absorbers and allowing for movement. Since the entire weight of the torso is supported by the vertebral column, and the whole body weight is transmitted through the lumbar spine. Because of this, the lower segment vertebrae are most susceptible to degenerative changes. This causes deformities of this region as the age advances in many individuals. Proper correction of deformity is challenging. There have been advances in spinal fusion procedures and interspinous implantation of devices including pedicle screws.